Gauze Impregnated With Quaternary Ammonium Salt Reduces Bacterial Colonization of Surgical Drains After Breast Reconstruction. (June 2018) - Strong, Amy L.; Wolfe, Emily T.; Shank, Nina; Chaffin, Abigail E.; Jansen, David A.
Abstract : Abstract: Surgical site infection after breast reconstruction is associated with increased length of hospital stay, readmission rates, cost, morbidity, and mortality. Identifying methods to reduce surgical site infection without the use of antibiotics may be beneficial at reducing antimicrobial resistance, reserving the use of antibiotics for more severe cases. Quaternary ammonium salts have previously been shown to be a safe and effective antimicrobial agent in the setting of in vitro and in vivo animal experiments. A retrospective study was conducted to investigate the antimicrobial properties of a quaternary ammonium salt, 3-trimethoxysilyl propyldimethyloctadecyl ammonium chloride (QAS-3PAC; Bio-spear), at reducing surgical drain site colonization and infection after breast reconstruction (deep inferior epigastric perforator flap reconstruction or tissue expander placement). Twenty patients were enrolled, with 14 surgical drains covered with nonimpregnated gauze and 17 surgical drains covered with QAS-3PAC impregnated gauze, for the purposes of investigating bacterial colonization. Antibiotic sensitivity analysis was also conducted when bacterial cultures were positive. The overall incidence of bacterial colonization of surgical drains was lower in the treatment group compared with the control group (17.6% vs 64.3%, respectively; P = 0.008). QAS-3PAC impregnated gauze reduced the incidence of bacterial colonization of surgical drains during the first (0.0% vs 33.3%) and second (33.3% vs 87.5%; P = 0.04) postoperative week. Furthermore, no enhanced antibiotic resistance was noted on drains treated with QAS-3PAC impregnated gauze. The results of this study suggest that QAS-3PAC impregnated gauze applied over surgical drains may be an effective method for reducing the incidence of bacterial colonization.